Radiation‐Associated Sarcoma of the Head and Neck: Incidence, Latency, and Survival. (15th November 2021) - Smith, Joshua B.; Cass, Lauren M.; Simpson, Matthew C.; Osazuwa‐Peters, Nosayaba; Ward, Gregory M.; Massa, Sean T.
Abstract : Objectives/Hypothesis: Radiation‐associated sarcomas of the head and neck (RASHN) are known but rare sequelae after radiation for squamous cell carcinoma. The purpose of this study was to characterize RASHN, estimate the risk of RASHN in head and neck squamous cell patients after therapeutic radiation, and compare their survival to that of patients with de novo sarcomas of the head and neck (dnSHN). Study Design: Retrospective database analysis. Methods: RASHN and dnSHN cases were collected from the Surveillance, Epidemiology, and End Results Database to identify risk factors and calculate incidence and latency. Survival was compared between RASHN and dnSHN. Results: The risk of RASHN was 20.0 per 100, 000 person‐years. The average latency period was 124.2 months (range 38–329). The cumulative incidence of RASHN at 20 years was 0.13%. Oral cavity and oropharynx primaries demonstrate increased risk. Five‐year overall survival of RASHN was 22.4% compared to 64.5% for dnSHN. Conclusions: RASHN are confirmed to be rare. RASHN have poor overall survival and worse survival compared to dnSHN. The impact of intensity‐modulated radiation therapy protocols on this risk is unknown. Modifiable risk factors of smoking and alcohol consumption continue to dwarf radiation therapy as risk factors of second primary head and neck cancers. Level of Evidence: 3 Laryngoscope, 132:1034–1041, 2022